2013
DOI: 10.1016/j.jnucmat.2013.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of hydrogen isotopes in radiation defects formed in tungsten by neutron and ion irradiations

Abstract: Retention of D in neutron-irradiated W and desorption were examined after plasma exposure at 773 K. Deuterium was accumulated at a relatively high concentration up to a large depth of 50-100 m due to the trapping effects of defects uniformly induced in the bulk. A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 21 publications
(50 reference statements)
4
42
0
18
Order By: Relevance
“…It has been found that (i) at the damage levels in the range from 0.1 to 50 dpa, the concentration of the W-ion-induced defects demonstrates very weak dependence on the number of displacements per atom, and (ii) the quasi-saturation concentration of the W ion-induced defects decreases twice as the W-ion irradiation temperature increases from 300 to 573 K. were published earlier in Ref. [21].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It has been found that (i) at the damage levels in the range from 0.1 to 50 dpa, the concentration of the W-ion-induced defects demonstrates very weak dependence on the number of displacements per atom, and (ii) the quasi-saturation concentration of the W ion-induced defects decreases twice as the W-ion irradiation temperature increases from 300 to 573 K. were published earlier in Ref. [21].…”
Section: Discussionmentioning
confidence: 73%
“…It has been experimentally shown [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] that irradiation of W materials with 0.2-20 MeV H, He, Si, and W ions leads to an enhancement of hydrogen isotope retention in comparison with undamaged materials. However, damage created by ions is concentrated in a narrow region below the surface (in the damaged zone), while neutron-induced damage extends to larger depths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in D retention with neutron irradiation was observed even at a damage level as low as 0.025 dpa, and the D concentration in n-irradiated W reached values of 0.1-0.2 at% at all temperatures examined [3,7]. The desorption of D from nirradiated specimens continued up to temperatures above 1173 K, while that from nonirradiated specimen was completed at ≈700K after plasma exposure at 473K [2] and at ≈970K after exposure at 773K [6]. The activation energy for D detrapping, E det , from defects that contribute to dominant trapping at 773K was evaluated to be ≈1.8 eV [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…The desorption of D from nirradiated specimens continued up to temperatures above 1173 K, while that from nonirradiated specimen was completed at ≈700K after plasma exposure at 473K [2] and at ≈970K after exposure at 773K [6]. The activation energy for D detrapping, E det , from defects that contribute to dominant trapping at 773K was evaluated to be ≈1.8 eV [6,7]. However, the retention of hydrogen isotopes at a higher damage level has not been examined.…”
Section: Introductionmentioning
confidence: 99%